2017
DOI: 10.1017/jfm.2017.567
|View full text |Cite
|
Sign up to set email alerts
|

A Lagrangian fluctuation–dissipation relation for scalar turbulence. Part I. Flows with no bounding walls

Abstract: An exact relation is derived between scalar dissipation due to molecular diffusivity and the randomness of stochastic Lagrangian trajectories for flows without bounding walls. This "Lagrangian fluctuation-dissipation relation" equates the scalar dissipation for either passive or active scalars to the variance of scalar inputs associated to initial scalar values and internal scalar sources, as those are sampled backward in time by the stochastic Lagrangian trajectories. As an important application, we reconside… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…We briefly recall some results connected to the formulation (34), (35). First, a different perspective on the Constantin-Iyer-Kelvin theorem was explored by Eyink in [11], where it is shown that (34) arises as a consequence of Noether's theorem via the particle relabelling symmetry of a certain stochastic action 1 Rather than introduce the back-to-labels map, the Constantin-Iyer Kelvin theorem can also be naturally stated in terms of time-reversed Brownian motion and backwards Itô SDEs [12]. For detailed discussions of backward stochastic flows, see [16,17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We briefly recall some results connected to the formulation (34), (35). First, a different perspective on the Constantin-Iyer-Kelvin theorem was explored by Eyink in [11], where it is shown that (34) arises as a consequence of Noether's theorem via the particle relabelling symmetry of a certain stochastic action 1 Rather than introduce the back-to-labels map, the Constantin-Iyer Kelvin theorem can also be naturally stated in terms of time-reversed Brownian motion and backwards Itô SDEs [12]. For detailed discussions of backward stochastic flows, see [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…principle for the deterministic incompressible Navier-Stokes equations. See also [12] for a reformulation of Navier-Stokes as a system of stochastic Hamilton's equations, which yield a particularly simple derivation of the statistical Kelvin theorem. This formulation has been since extended to domains with solid boundary [13] and to a Riemannian manifold when the de Rham-Hodge Laplacian is the viscous dissipation operator [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown by those authors in a synthetic model of turbulence that the Lagrangian trajectories become "spontaneously stochastic" in the high Reynoldsnumber limit, with randomness of trajectories persisting even when the initial particle location and the advecting velocity become deterministic and perfectly specified. It has subsequently been shown that such "spontaneous stochasticity" of Lagrangian particle trajectories holds at Burgers shocks [111] and is necessary in incompressible Navier-Stokes turbulence for anomalous dissipation of passive scalars [112,113]. These considerations carry over directly to relativistic fluid world-lines X µ (X 0 , τ ) defined by the equations…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…if and only if u solves the viscous and forced Burgers' equation (2.9). After this manuscript was completed, the author was pointed out that this also follows from an application of the work by Drivas and Eyink in [17].…”
Section: Proposition 23 Let ω = R 3 Consider the 3-d Damped Eulermentioning
confidence: 88%